EZH2 Might Affect Macrophage Chemotaxis and Anti-Inflammatory Factors by Regulating CCL2 in Dental Pulp Inflammation - Ziqi Hu; Yingyi Chen; Jie He; He Liu; Tianqian Hui (Stem Cells International)
Objectives. We aimed to evaluate the effects of Enhancer of Zeste Homolog 2 (EZH2) on regulation of macrophage migration and expression of anti-inflammatory genes in pulpitis. Methods. Dental pulp inflammation was verified by histology in rat pulpitis model induced by lipopolysaccharide (LPS). Immunohistochemistry staining was used to detect changes of the expression of EZH2 and tumor necrosis factor alpha (TNF-α) in dental pulp inflammation. The expression of EZH2, CCL2, and cluster of differentiation 68 (CD68: macrophage surface marker) was measured by immunofluorescence staining. The effect of EZH2 on microphage migration was assessed by cell migration assay. The expressions of anti-inflammatory cytokine interleukins (IL-4 and IL-10) and transforming growth factor-β (TGF-β) in HDPCs which were treated by EZH2 complex, CCL2 complex, and CCL2 antibody were examined by quantitative real-time polymerase chain reaction (q-PCR). Results. The expression of TNF-α gradually increased in dental pulp inflammation. The expression of EZH2 in dental pulp decreased in 8 hours after LPS stimulation. However, the expression of EZH2 gradually increased in dental pulp after 1 day stimulation by LPS. The results of immunofluorescence staining showed that the expressions of EZH2, CCL2, and CD68 were significantly upregulated in dental pulp inflammation of rats. EZH2 could enhance macrophage migration. And the chemotactic activity of macrophages exposed to supernatants of EZH2-treated HDPCs could be inhibited by CCL2 inhibition. In addition, EZH2 suppressed the expression of anti-inflammatory genes, but CCL2 inhibition reversed the downregulation of anti-inflammatory factors, including IL-4 and TGF-β in HDPCs. Conclusions. EZH2 might affect chemotaxis of macrophages and the expression of anti-inflammatory factors by regulating CCL2. EZH2 plays an important role in the development of dental pulp inflammation, and it might be as a target for treatment of pulpitis.